2007
DOI: 10.1096/fj.06-7440com
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia up‐regulates the angiogenic cytokine secretoneurinviaan HIF‐1α‐ and basic FGF‐dependent pathway in muscle cells

Abstract: Expression of angiogenic cytokines like vascular endothelial growth factor is enhanced by hypoxia. We tested the hypothesis that decreased oxygen levels up-regulate the angiogenic factor secretoneurin. In vivo, muscle cells of mouse ischemic hind limbs showed increased secretoneurin expression, and inhibition of secretoneurin by a neutralizing antibody impaired the angiogenic response in this ischemia model. In a mouse soft tissue model of hypoxia, secretoneurin was increased in subcutaneous muscle fibers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
(44 reference statements)
8
41
0
1
Order By: Relevance
“…We also could show that SN is upregulated in skeletal muscle cells by hypoxia via an indirect, b-FGF-and hypoxia-inducible factor 1-␣-dependent pathway. 17 In this work, we also demonstrated that inhibition of SN worsened the physiological angiogenic response in the hindlimb ischemia model. Recently, a beneficial effect of SN was reported in murine stroke models, resulting in antiapoptotic effects of SN on neuronal cells mediated by the Jak/Stat pathway, resulting from effects on stem cells and induction of angiogenesis.…”
supporting
confidence: 58%
“…We also could show that SN is upregulated in skeletal muscle cells by hypoxia via an indirect, b-FGF-and hypoxia-inducible factor 1-␣-dependent pathway. 17 In this work, we also demonstrated that inhibition of SN worsened the physiological angiogenic response in the hindlimb ischemia model. Recently, a beneficial effect of SN was reported in murine stroke models, resulting in antiapoptotic effects of SN on neuronal cells mediated by the Jak/Stat pathway, resulting from effects on stem cells and induction of angiogenesis.…”
supporting
confidence: 58%
“…Although this secretory protein has been extensively used as a marker of the regulated secretory pathway (53,57,58), its function in the formation of DCGs has not been carefully investigated, and so far it remains elusive (19,22). By analyzing the consequences of SgII down-regulation in the neuroendocrine PC12 cell line, and its ability to rescue a regulated secretory pathway in the secretory-deficient PC12 variant A35C, we demonstrate the importance of SgII for DCG biogenesis in neuroendocrine cells and characterize fundamental features of SgIImediated granulogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence gathered so far reports the formation of granule-like structures in the fibroblast-like COS-1 cell line (19), and a vesicular distribution of secretoneurin immunoreactivity in ischemic mouse muscle fibers (22). Common genetic variation at the human SCG2 locus modulates SgII transcriptional expression, which correlates with blood pressure elevation (2).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that hypoxia up-regulates HIF-1a, VEGF, and FGF-2 expression in tissue and shows positive correlation with the tissue repair process. 15,27,28 In normal and transformed cell lines, HIF-1a has been identified as the master regulator of the transcriptional response to oxygen deprivation, 29 and regulates the expression of numerous target genes that control angiogenesis, including VEGF.…”
Section: Reparative Reaction In Osteonecrosis Of the Femoral Headmentioning
confidence: 99%